Religious Gratitude, Hope, and Post-Traumatic Growth after Diagnosis of Cardiovascular Disease - Gulzar, Iqra; Iqbal, Muhammad Nasar; Latif, Hafiz Salman (Annals of Human and Social Sciences, 2023)
In the realm of psychological and spiritual well-being, this research delves into the intricate dynamics of religious gratitude, hope, and post-traumatic growth. The present study was conducted with the aim to find out the relationship between religious gratitude, hope and post-traumatic growth among patients of cardiovascular disease. Data was collected from the Lahore and Multan cardiology hospitals. A cross-sectional based correlational research design was used. The sample consisted of (N=100) cardiac patient and it was collected by using non- probability purposive sampling technique. The age range of the sample was 35 to 60 years. Data was collected by using three tools i.e., Religious Gratitude Scale (RG), Adult Hope scale (AHS) and Post-Traumatic Growth Inventory (PGTI). The result revealed that there was significant positive relationship among religious gratitude, hope and post-traumatic growth in diagnosed patients with cardiovascular disease. Understanding the role of religious gratitude and hope can inform healthcare providers on how to incorporate spiritual and psychological support into patient care plans. This may lead to more holistic, patient-centered approaches that promote emotional well-being alongside medical treatment.